NEW TECHNIQUE FOR THE REMOVAL OF UNSATURATED FATTY OIL OF PLUKENETJA VOLUBILIS L. "SACHA INCHI" - Huamán M., Juana M. (2009)
This technique has only been used for the extraction of fish oil, it consisted in the alkaline hydrolysis of glycerides using a rate of 50% KOH for saponification and methylene chloride to extract the unsaponificable part. After saponification and the formation of the sal!, it is acidified to obtain free fatty acids, using acetic acid al temperatures lowers !han -20 ºC. Following the extraction the organic phase containing free fatty acids are dissolved in acetone and temperature used -20ºC ( 20 celsius) precipitates the saturated fatty acids and they are separated by filtration. lt is purified using magnesium salts dissolved in acetone, which means that the unsaturated fatty acids are more soluble. This sample was tested with quality controls like the lodine index, giving much higher values (196) from the once we started (192). lt was also analyze with a GC IS05509-2000 and ISO 5508-1990 which determined a 97.05% of unsaturated fatty acids, from which linolenic acid (omega 3) represents a 50.4%, línoleic acid (omega 6) represents 37.66% and 8,73% of oleic acid.